The Effect of Good Corporate Governance and Financial Distress on the Integrity of Financial Statements with Audit Quality as a Mediation Variable - Made Ayu Prilla Winda Puspita; Ni Made Dwi Ratnadi; Made Gede Wirakusuma; Ida Bagus Putra Astika (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The information in the financial statements must be presented fairly, honestly, and fairly disclose facts to users in order to produce financial statements with integrity. The purpose of this study was to examine the effect of good corporate governance and financial distress on the integrity of financial statements through audit quality. The population in this study are consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The number of samples obtained as many as 66 companies with purposive sampling method. The data analysis technique used is multiple linear regression and the selection of good corporate governance proxies using factor analysis. Based on the results of the analysis, it was found that good corporate governance has an effect on the integrity of financial statements. Financial distress affects the integrity of financial statements. Audit quality affects the integrity of financial statements. Good corporate governance affects the integrity of financial statements through audit quality. Financial distress affects the integrity of financial statements through audit quality. This shows that the increasing audit quality allows a reduction in financial distress that occurs in the company so as to produce financial statements with integrity.